The pattern of anti-tuberculosis drug resistance in pulmonary tuberculosis patients - Rijal, K.R.; Ghimire, P.; Rijal, B.; Bam, D.S. (Journal of Institute of Medicine Nepal, 2007)
Background: Tuberculosis is one of the major public health problems in Nepal. Drug resistant tuberculosis has posed a serious challenge in TB control program. Drug resistance tuberculosis is the most difficult for the treatment and cure of the patient. Objective: To find out the current situation of drug resistant pattern at national tuberculosis center, Nepal. Design: Central Department of Microbiology, Tribhuvan University in collaboration with NTC, STC, conducted a prospective study. Methods: One hundred ninety-nine Mycobacterium tuberculosis isolated from the sputumin national tuberculosis center (NTC) were studied to find out the drug resistant pattern by utilizing absolute concentration method. Results: Of the 199 culture positive strains were tested, 161from previously treated cases and 38 from new cases. Overall primary and acquired resistance were 36.82%and 75.05%respectively. The study showed that the Primary drug resistance (PDR) to one drug was found to be 23.67%, to two drugs was 10.52%, to three drugs was 0%, and four drugs was 2.63%where as acquired drug resistance (ADR) to one drug was 32.38%, to two drug was 19.19%, to three drugs was 11.78%, to four drugs was 11.80%. Primary and acquired multi-drug resistance (MDR)) was in 2.63%and 19.25% of the isolates respectively Conclusion: Overall, drug resistance of M. tuberculosis is high. It is concluded that regular monitoring of MDR–TB and making policy according to research finding is necessary as it is changing every year, which helps to control MDR-TB. Journal of Institute of Medicine Vol.27(3) 2005